Using detrital zircon and rutile to constrain sedimentary provenance of Early Paleozoic fluvial systems of the Araripe Basin, Western Gondwana - Cerri, Rodrigo I. [UNESP] (2022)
The Early Paleozoic of the NE Brazilian sedimentary basins are key to understanding the primeval depositional environments and paleogeography of Western Gondwana after its final assembly. In this context, determining the sedimentary provenance of the Early Paleozoic Cariri Formation (basal unit of the Araripe Basin) may improve paleogeographic reconstructions and stratigraphic correlations. Despite the Araripe Basin being one of the best-studied interior basins of northeastern Brazil, the Cariri Formation lacks detailed geochronological and sedimentary provenance analyses, which hamper precise definitions of its depositional age, sedimentary source areas and paleogeography. Considering this scenario, we performed a combined multiproxy approach, including sedimentologic and stratigraphic analysis, detrital zircon U–Pb dating and provenance studies based on trace elements in detrital rutile. The maximum depositional age for the Cariri Formation suggests that its sedimentation started after the Late Cambrian. Detrital zircon ages and detrital rutile provenance indicate that the primary source areas for the Cariri Formation fluvial system were the orogenic terranes related to the Brasiliano Orogeny, located at the SE of the Borborema Province (e.g., Sergipano Belt), with secondary, but also important, the contribution of Cambrian sources. Records of this event are also found in northern Africa, where units related to the Neoproterozoic East African-Antarctic and Pan African orogens provided sediments for basin-scale fluvial systems.